Vanilla Callogenesis with the Addition of Picloram and BAP under Dark and Light Conditions - Bahrunnisa, Atiqah; Noor Aini Habibah (Universitas Negeri Semarang, 2025)
Vanillin is a secondary metabolite in vanilla, with a 1%–3% content. Tissue culture is an effective alternative for producing plant secondary metabolites. This study aimed to analyze the effect of picloram and BAP under light and dark conditions on the callogenesis of vanilla leaf explants. A randomized block design was used with two factors: picloram concentration (0 ppm, 2.5 ppm, 5 ppm, 7.5 ppm) and BAP (0 ppm, 1 ppm, 2 ppm, 3 ppm), as well as lighting conditions (light and dark). Vanilla leaf explants were cultured on MS medium and incubated for three months. The observed parameters included the time for explants to curve, the percentage of curved explants, the time of callus formation, the percentage of callus-forming explants, and callus morphology. The results showed that PGRs type/concentration significantly affected the percentage of curved explants but had no significant effect on other parameters. Lighting and its interaction with PGRs had no significant effect. The best combination of picloram and BAP resulted in 100% curved explants but was less optimal for inducing callus formation in vanilla leaf explants. This study can open scientific insights into the combination of picloram and BAP and the effects of different lighting in vanilla leaf callogenesis.